The female right to education in the age of globalization - González-Peláez, Marta; Tomás, Cristina (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Gender equality is a global priority for UNESCO closely linked to the Organization’s efforts to promote girls’ right to education so that they acquire the same skills in and through education. There are, depending on the context (levels of education and instruction) and geographical location, great gender inequalities in access, learning achievement and continuation of education, with girls generally being the most disadvantaged. Despite the gains made, there are more girls out of school than boys - 16 million girls will never go to school (UNESCO Institute for Statistics) - and women make up two-thirds of the 750 million adults who they lack basic literacy skills.